Strategies for Maintaining Local Identity During Globalization: A Study of Urban Communities - A. Fikri Ainurrizqi; Gondo Yumitro (Journal of Innovation, Business Management and Entrepreneurship, 2025)
This article explores the challenges urban communities face in preserving local identity amid the rapid currents of globalization. Globalization exerts significant influence through the erosion of traditional cultural values, the dominance of mass popular culture, and the weakening of local spiritual practices. Employing a qualitative approach and literature review, the study investigates various strategies that can help communities sustain their cultural roots. These include implementing culture-based education, strengthening local spiritual and religious communities, revitalizing cultural public spaces, and engaging the younger generation in cultural preservation efforts. The findings indicate that local identity can endure when communities engage in adaptive and sustainable cultural resistance. Rather than rejecting globalization outright, the article emphasizes the importance of a critical and creative response that integrates local values with global influences. In conclusion, this article presents several practical recommendations for maintaining Indonesia’s rich and diverse cultural identity in the face of increasingly globalized societal dynamics.